ASUPAN LEMAK, OBESITAS SENTRAL DAN HIPERKOLESTEROLEMIA PADA APARATUR SIPIL NEGARA (ASN) PEMERINTAH DAERAH PROVINSI BALI - Wiardani, Ni Komang; Kusumajaya, A.A. Ngurah (PERSATUAN AHLI GIZI INDONESIA, 2018)
Central obesity is a type of obesity that is closely related to elevated cholesterol levels as one indicator of metabolic syndrome. Central obesity is found in many communities including ASN (government employee) along with changes in diet and community work patterns. The objective of this study was to investigate the relationship between fat intake, central obesity and cholesterol levels among government employee of the ProvincialOffice of Bali. This was an observational study with a cross-sectional design. The number of the subjects involved were 210 people, determined by multistage random sampling. The data collected were food intake, waist circumference and blood cholesterol level.Results showed that 58.1 percent were female and 41.9 percent male with age average of 43.6 years. The average total fat intake was 63.7 g, saturated fat was 25.7 g, cholesterol was 283.3 mg, waist circumference was 84.8 cm and total cholesterol was 183. 6 mg/dl. About 38.6 percent fat intakes were above adequacy, 44.8 percent subjects had central obesity and 34.3 percent of them had cholesterol level above normal (hypercholesterolemia). There was a significant correlation between total fat intake, saturated fat, cholesterol and central obesity with hypercholesterolemia status (p 0.05) and central obesity was the main determinant of Hypercholesterolemia (p 0.05). It was concluded that central obesity related to hypercholesterolemia among the employee of Bali Provincial Office.